2010
DOI: 10.1080/13674670802187912
|View full text |Cite
|
Sign up to set email alerts
|

Personality and religious orientation: shifting sands or firm foundations?

Abstract: SummaryBeit-Hallami and Argyle (1997) concluded that individual differences in religiosity are inversely related to psychoticism but independent of extraversion and neuroticism. The aim of the present study is to test the generalisability of that conclusion within the context of Eysenck"s dimensional model of personality by distinguishing between different conceptualisations of religiosity and by distinguishing between different overall levels of religiosity in the sample. A total of 517 undergraduate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 57 publications
4
17
0
1
Order By: Relevance
“…A number of recent studies have demonstrated, for example, that Eysenck's three dimensional model of personality (Eysenck & Eysenck, 1991) is able to predict individual differences in religiosity, including studies among school pupils (Francis & Wilcox, 1994, 1996Smith, 1996;Fearn, Lewis & Francis, 2003;Williams, Robbins, & Francis, 2005Francis, Williams, & Robbins, 2009, 2010, students (Maltby, 1995;Lewis & Maltby, 1996;Francis, 1997Francis, , 2010, school teachers (Francis & Johnson, 1999), senior citizens (Francis & Bolger, 1997), and the general adult population (Kaldor, Francis, & Fisher, 2002).…”
Section: Influence Of Personalitymentioning
confidence: 99%
“…A number of recent studies have demonstrated, for example, that Eysenck's three dimensional model of personality (Eysenck & Eysenck, 1991) is able to predict individual differences in religiosity, including studies among school pupils (Francis & Wilcox, 1994, 1996Smith, 1996;Fearn, Lewis & Francis, 2003;Williams, Robbins, & Francis, 2005Francis, Williams, & Robbins, 2009, 2010, students (Maltby, 1995;Lewis & Maltby, 1996;Francis, 1997Francis, , 2010, school teachers (Francis & Johnson, 1999), senior citizens (Francis & Bolger, 1997), and the general adult population (Kaldor, Francis, & Fisher, 2002).…”
Section: Influence Of Personalitymentioning
confidence: 99%
“…In the EPP, both Hills et al and Francis found it positively related to QRO (Hills et al 2004;Francis 2010). In the BFI, Henningsgaard and Arnau noted the same (Henningaard and Arnau 2008).…”
Section: Empirical Investigations Of Qro and Personality Traitsmentioning
confidence: 65%
“…However, Francis noted quest religion was associated with low extraversion and not associated with psychoticism (Francis 2010). With the Big Five Inventory (BFI), Henningsgaard and Arnau found QRO related to high neuroticism, high openness, and low conscientiousness (John et al 1991;Henningaard and Arnau 2008).…”
Section: Empirical Investigations Of Qro and Personality Traitsmentioning
confidence: 99%
“…Además, el estudio de las orientaciones religiosas ha contribuido a conocer sus relaciones con la salud mental (Ghorbani, Watson, Chen & Norballa, 2012;Kuyel, Cesur & Ellison, 2012;Maltby et al, 2010). Diferentes autores sugieren que la orientación intrínseca hacia la religión (en la que la religión es fundamental para el individuo) se asocia con un mayor bienestar subjetivo, mientras que una orientación extrínseca hacia la religión (en la que la religión es una meta para alcanzar objetivos personales y sociales) se asocia con emociones negativas, ansiedad o depresión (Dias, 2011;Ellis & Wahab, 2013;Francis, 2010;Koenig, George & Titus, 2004;Pössel et al, 2011;Wulff, 1997).…”
unclassified